Printed Borders for Sixteenth-Century Music or Music Paper and the Early Career of Music Printer Thomas East. (14th June 2018) - Butler, Katherine
Abstract: Images of printed books online makes it increasingly possible to trace the use of specific printing types and design features across a wide range of publications to reveal new information about the working practices of Elizabethan printers. This study concerns two of these: the fleuron and the blank printed music stave. In the second half of the sixteenth century, an increasing number of music copyists chose to write their manuscripts on to paper with printed music staves. A subset of these music papers contains decorative fleuron borders that might be used to attribute them to specific printers or time-frames through comparison with other printed materials. This paper traces the history of three varieties of bordered music paper and explores the potential functions of framing staves in this way with regard to both music paper and printed music collections.